Application of ICD‐PM to preterm‐related neonatal deaths in South Africa and United Kingdom. (16th August 2016) - Allanson, ER; Vogel, JP; Tunçalp, Ӧ; Gardosi, J; Pattinson, RC; Francis, A; Erwich, JJHM; Flenady, VJ; Frøen, JF; Neilson, J; Quach, A; Chou, D; et al.
Abstract : Objective: We explore preterm‐related neonatal deaths using the WHO application of the International Classification of Disease (ICD‐10) to deaths during the perinatal period: ICD‐PM as an informative case study, where ICD‐PM can improve data use to guide clinical practice and programmatic decision‐making. Design: Retrospective application of ICD‐PM. Setting: South Africa, and the UK. Population: Perinatal death databases. Methods: Descriptive analysis of neonatal deaths and maternal conditions present. Main outcome measures: Causes of preterm neonatal mortality and associated maternal conditions. Results: We included 98 term and 173 preterm early neonatal deaths from South Africa, and 956 term and 3248 preterm neonatal deaths from the UK. In the South African data set, the main causes of death were respiratory/cardiovascular disorders (34.7%), low birthweight/prematurity (29.2%), and disorders of cerebral status (25.5%). Amongst preterm deaths, low birthweight/prematurity (43.9%) and respiratory/cardiovascular disorders (32.4%) were the leading causes. In the data set from the UK, the leading causes of death were low birthweight/prematurity (31.6%), congenital abnormalities (27.4%), and deaths of unspecified cause (26.1%). In the preterm deaths, the leading causes were low birthweight/prematurity (40.9%) and deaths of unspecified cause (29.6%). In South Africa, 61% of preterm deaths resulted from the maternal condition of preterm spontaneous labour. Among the preterm deaths in the data set from the UK, no maternal condition was present in 36%, followed by complications of placenta, cord, and membranes (23%), and other complications of labour and delivery (22%). Conclusions: ICD‐PM can be used to appraise the maternal and newborn conditions contributing to preterm deaths, and can inform practice. Tweetable abstract: ICD‐PM can be used to appraise maternal and newborn contributors to preterm deaths to improve quality of care. Tweetable abstract: ICD‐PM can be used to appraise maternal and newborn contributors to preterm deaths to improve quality of care.